2023
DOI: 10.3389/fmicb.2023.1190894
|View full text |Cite
|
Sign up to set email alerts
|

Causal Effects between Gut Microbiome and Myalgic Encephalomyelitis/Chronic Fatigue Syndrome: A Two-Sample Mendelian Randomization Study

Abstract: BackgroundEvidence from previous studies have implicated an important association between gut microbiota (GM) and Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS), but whether there is a definite causal relationship between GM and ME/CFS has not been elucidated.MethodThis study obtained instrumental variables of 211 GM taxa from the Genome Wide Association Study (GWAS), and mendelian randomization (MR) study was carried out to assess the effect of gut microbiota on ME/CFS risk from UK Biobank GWAS (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Interestingly, a large proportion of ME/CFS patients (35 to 90%) have gastrointestinal complaints, which are often associated with the comorbidities IBS and IBD ( 34 ). Various studies have demonstrated intestinal dysbiosis in ME/CFS ( Table 1 ) ( 13 , 33 , 34 , 36 – 44 ), although uniform microbiome signatures are non-existent. This is mainly due to the high intra- and inter-individual variability of the microbiome.…”
Section: Intestinal Dysbiosis In Me/cfsmentioning
confidence: 99%
“…Interestingly, a large proportion of ME/CFS patients (35 to 90%) have gastrointestinal complaints, which are often associated with the comorbidities IBS and IBD ( 34 ). Various studies have demonstrated intestinal dysbiosis in ME/CFS ( Table 1 ) ( 13 , 33 , 34 , 36 – 44 ), although uniform microbiome signatures are non-existent. This is mainly due to the high intra- and inter-individual variability of the microbiome.…”
Section: Intestinal Dysbiosis In Me/cfsmentioning
confidence: 99%
“…The relationship between host genetic factors and the gut microbiome in the context of BTC necessitates more comprehensive exploration. Mendelian Randomization (MR), a prevalent analytical technique employed for investigating causal linkages between exposure variables and resultant outcomes, has been utilized to probe prospective causal affiliations between gut microbiota and a diverse array of medical conditions (Liu et al, 2023;Xi et al, 2023;Min et al, 2023;He et al, 2023;Li et al, 2023;Luo et al, 2023b). Consequently, we endeavored to ascertain the causal linkage between these variables at the genetic level through the application of MR techniques.…”
Section: Introductionmentioning
confidence: 99%